2016
DOI: 10.1007/s12020-016-1041-3
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins 6 and 8 and abdominal fat depots are distinct correlates of lipid moieties in healthy pre- and postmenopausal women

Abstract: Purpose Available data associate lipids concentrations in men with body mass index (BMI), anabolic steroids, age, and certain cytokines. Data are less clear in women, especially across the full adult lifespan, and when segmented by pre- and postmenopausal status. Methods Subjects: 120 healthy women (60 pre- and 60 postmenopausal) in Olmsted County, MN, USA, a stable well studied clinical population. Dependent variables: measurements of 10-hr fasting high-density lipoprotein cholesterol (HDL-C), total cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
2
0
1
Order By: Relevance
“…IL-6 levels correlated to BMI only in postmenopausal women, but both IL-6 and hs-CRP showed no marked interaction in the majority of analyzes. A previous study found a correlation between lipid markers and IL-6 [29], and this might explain the positive correlation observed here. Notably, a high-intensity training intervention was shown to increase IL-6 while reducing visceral adiposity tissue in postmenopausal women [30].…”
Section: Discussionsupporting
confidence: 76%
“…IL-6 levels correlated to BMI only in postmenopausal women, but both IL-6 and hs-CRP showed no marked interaction in the majority of analyzes. A previous study found a correlation between lipid markers and IL-6 [29], and this might explain the positive correlation observed here. Notably, a high-intensity training intervention was shown to increase IL-6 while reducing visceral adiposity tissue in postmenopausal women [30].…”
Section: Discussionsupporting
confidence: 76%
“…In addition to a significant increase in LBM, a significant decrease in BF% and central adiposity was noted following the exercise program. Interestingly, the decrease in overall body fat and waist circumference may be considered a primary mechanism for improvement in the metabolic and blood lipid profile, and BP in the present study (Arnarson et al, 2014;Coelho et al, 2013;Colman et al, 1995;Fenicchia et al, 2004;Mandrup et al, 2018;Philipsen et al, 2015;Veldhuis et al, 2016;Zhou and Qin, 2012), thereby contributing to the reduction of risk of MetS in this population.…”
Section: Body Compositionmentioning
confidence: 55%
“…The mechanisms by which blood lipid levels improved in the present study remains unclear, however, several relationships may be partially responsible for these improvements. Abdominal fat mass accumulation has been positively correlated with LDL and TC levels (Veldhuis et al, 2016). Changes in body composition following resistance training, such as reduced BF% and increased LBM, have been reported to play a role in improving blood lipid profiles in older adults (Arnarson et al, 2014).…”
Section: Blood Lipid Profilementioning
confidence: 99%
“…A IL-6 tem efeito direto na sinalização da insulina em adipócitos e hepatócitos, o que atrapalha a sua ligação aos receptores específicos, além de estimular a lipólise e a liberação de graxos livres na circulação 26 . Destaca-se também que a IL-6 pode induzir a RI por diminuição da secreção de adiponectina, uma importante citocina que atua beneficamente na ação da insulina 27 . Dados sugerem que, enquanto o TNF-alfa age de forma parácrina no adipócito, a IL-6 circula no plasma em concentrações relativamente altas, sendo, portanto, muito mais importante sistemicamente, podendo ser chamada de citocina endócrina.…”
Section: Discussionunclassified